Recycling of textile waste by reinforcing earthy render with micro-fiber - Pinto, J. (2013)
Earth construction is worldwide spread. It is a valuable heritage to preserve because of its cultural and socio-economical relevance. Furthermore, earth construction, since it needs significantly less energy than modern construction techniques, and works with local materials, it contributes for thesustainable development. In Portugal, there is an impressive earth construction heritage that requires maintenance. Among the Portuguese traditional building techniques related to earth construction, the rammed earth, the adobe and the tabique are the most relevant ones. This work is focused on attempting to apply textile waste micro-fiber as an alternative sustainable reinforcement solution of earthy render of tabique walls. Therefore, several earthy render samples reinforced with 1% textile waste micro-fiber content were prepared and mechanically tested. The main experimental results are presented and discussed, and the main conclusions are drawn. This study also contributes for recycling a specific waste, namely short fibers from needling machines used to produce nonwoven fabrics.